UJICOBA model pemberdayaan lembaga perlindungan anak dalam pelayanan kesejahteraan anak Ikawati.....[ et al ]; konsultan, C.Elly Kumari Tjahya Putri - Ikawati; Putri, C.Elly Kumari Cahya (2008)
X 91 cm 21 cm